Hussein of Jordan : My War with Israel - Vance, Vick and Laurer, Pierre (London Peter Owen, 1969)
With extraordinary candor, the King of Jordan tells how and why his nation and his Arab allies were so badly beaten by Israel in the Six Day War of June, 1967
Include Illustration
Keywords: Israel-Arab War (1967) -- Israel